PENGARUH LATIHAN SEPAK BOLA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN - Zamawi, Muhammad Nur Farish (Jurnal Penelitian Anak Usia Dini, 2023)
This study aims to determine the effect of soccer training on gross motor development of children aged 5-6 years at Dharma Bakti Kindergarten Turipinggir, Jombang Regency.. This research was conducted experimentally by involving educators as collaborators. The research subjects consisted of 12 boys, who were students in group B TK Dharma Bakti. The object of this research is the development of children's gross motor skills through soccer training activities. This research uses a quantitative type approachLike an experimentresearch design "One-Group Pretest-Posttest Design”. Researchers choose the type of researchQuasi ExperimentalServes as a comparison before receiving treatment and after receiving treatment(pretest-posttest) soccer training on gross motor development. Data was collected through observation, pretest, posttest, and documentation. Data analysis used the method of data normality test and homogeneity test and hypothesis testing. Based on the results of this study, it can be concluded that soccer training can be used as a physical learning strategy to help children develop gross motor skills, increase their ability to move more actively, improve basic movement skills, improve health, and improve intelligence. Plus, soccer practice can be a fun activity for kids.